Journey to the Center of the Cell: Current Nanocarrier Design Strategies Targeting Biopharmaceuticals to the Cytoplasm and Nucleus - V. Munsell, Erik; L. Ross, Nikki; O. Sullivan, Millicent (Current Pharmaceutical Design, 2016)
New biopharmaceutical molecules, potentially able to provide more personalized and effective treatments, are being identified through the advent of advanced synthetic biology strategies, sophisticated chemical synthesis approaches, and new analytical methods to assess biological potency. However, translation of many of these structures has been significantly limited due to the need for more efficient strategies to deliver macromolecular therapeutics to desirable intracellular sites of action. Engineered nanocarriers that encapsulate peptides, proteins, or nucleic acids are generally internalized into target cells via one of several endocytic pathways. These nanostructures, entrapped within endosomes, must navigate the intracellular milieu to orchestrate delivery to the intended destination, typically the cytoplasm or nucleus. For therapeutics active in the cytoplasm, endosomal escape continues to represent a limiting step to effective treatment, since a majority of nanocarriers trapped within endosomes are ultimately marked for enzymatic degradation in lysosomes. Therapeutics active in the nucleus have the added challenges of reaching and penetrating the nuclear envelope, and nuclear delivery remains a preeminent challenge preventing clinical translation of gene therapy applications. Herein, we review cutting-edge peptide- and polymer-based design strategies with the potential to enable significant improvements in biopharmaceutical efficacy through improved intracellular targeting. These strategies often mimic the activities of pathogens, which have developed innate and highly effective mechanisms to penetrate plasma membranes and enter the nucleus of host cells. Understanding these mechanisms has enabled advances in synthetic peptide and polymer design that may ultimately improve intracellular trafficking and bioavailability, leading to increased access to new classes of biotherapeutics.
Keywords: Polymeric and peptide nanocarriers